NEEL: Núcleo de Estudos e Extensão em Leite - Sousa, Osvaldo Alex de [UNESP]; Dellaqua, João Victor Tino [UNESP]; Santi, Pedro Fernando [UNESP]; Pinto, Leandro Dias [UNESP]; Assumpção, Alice Helena Peres [UNESP]; Bosco, Daniela Monte Serrat [UNESP]; Santos, Anderson Augusto do [UNESP]; Tomaz, Lais de Aquino [UNESP]; Silva Filho, Wilson Inácio da [UNESP]; Millen, Danilo Domingues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Groups, or cores, studies whose main function together undergraduates, graduate and trained technicians and farmers to discuss and deepen issues and common interest. There are numerous study groups in several areas that are of great importance for the academic training of students in university. Including The Center for Studies and Extension milk (NEEL), a team of animal husbandry course of graduate students at UNESPDracena, forming a board of directors responsible for organizing events and lecture the minister group at the University openly coordinated also by the teacher responsible for the discipline of milk cattle and ruminant nutrition. NEEL is the oportuniade for students with an interest in the dairy cattle area devote time to activity during their academic training, developing responsibility and learning to work in teams, contributing to the formation of other colleagues and applying the theory discussed in room class to practical experience.

Os grupos, ou núcleos, de estudos têm como principal função reunir alunos de graduação, pósgraduação e técnicos formados e produtores rurais a fim de discutir e aprofundar assuntos de interesse comum. Existem inúmeros grupos de estudos em diversas áreas que são de grande importância para a formação acadêmica de alunos em universidade. Entre eles o Núcleo de Estudos e Extensão em Leite (NEEL), uma equipe composta por alunos de graduação do curso de Zootecnia da UNESP-Dracena, que formam uma diretoria responsável pela organização de eventos e palestras ministradas pelo grupo na universidade, coordenado também pelo professor responsável pela disciplina de bovinocultura de leite e nutrição de ruminantes. O NEEL é a oportunidade para que estudantes com interesse na área de bovinocultura de leite dediquem tempo à atividade durante a sua formação acadêmica, desenvolvendo responsabilidade e aprendendo a trabalhar em equipe, contribuindo para a formação dos demais colegas e aplicando a teoria discutida em sala de aula à vivência prática.
Keywords: Dairy cattle; Rural property; Assistance; Bovinocultura de leite; Propriedade rural; Assistência